Persistent Opioid Use Among Children, Adolescents, and Young Adults After Common Cleft Operations. Issue 7 (October 2018) - Bennett, Katelyn G.; Harbaugh, Calista M.; Hu, Hsou Mei; Vercler, Christian J.; Buchman, Steven R.; Brummett, Chad M.; Waljee, Jennifer F.
Abstract : Background: Surgical care represents an important source of opioid prescribing and chronic use, but rates of prolonged opioid use following pediatric procedures remain unclear. The authors describe the rates and risk factors for new persistent opioid use in patients after common cleft operations. Methods: The authors examined claims from the Truven Marketscan databases from January 1, 2010 to December 31, 2014. The authors included opioid-naive patients ages 8 to 25, who underwent 1 of 10 cleft-related procedures. Patients were considered opioid-naïve if they had no opioid prescription fills in the 11 months prior to the perioperative period. The authors obtained a random sample of age-matched, nonsurgical patients from the same dataset to be used as a control group. Included cleft patients had no procedural codes in the 6 months following surgery. All included patients filled an opioid prescription during the perioperative period, defined as 30 days before and 14 days after surgery. The primary outcome was new persistent opioid use, which is defined as continued opioid prescription fills between 90 and 180 days after the procedure. Results: This cohort included 2039 cleft patients and 2100 control patients. The incidence of new persistent opioid use following surgery was 4.4% and 0.1% in the control group. Higher odds of opioid use 3 months beyond surgery were associated with distractor placement (OR 5.34, CI 2.00–14.24, P = 0.001). Increasing age (OR 1.11, CI 1.04–1.17, P = 0.001) and presence of a gastrointestinal comorbidity (OR 7.37, CI 1.49–36.54, P = 0.014) were also associated with new persistent use. Conclusions: New persistent opioid use occurs after cleft-related procedures and could lead to chronic use in children, adolescents, and young adults.